Clinical radiography education across Europe. Issue 1 (September 2017) - England, A.; Geers-van Gemeren, S.; Henner, A.; Kukkes, T.; Pronk-Larive, D.; Rainford, L.; McNulty, J.P.
Abstract: Purpose: To establish a picture of clinical education models within radiography programmes across Europe by surveying higher education institutions registered as affiliate members of the European Federation of Radiography Societies (EFRS). Method: An online survey was developed to ascertain data on: practical training, supervisory arrangements, placement logistics, quality assurance processes, and the assessment of clinical competencies. Responses were identifiable in terms of educational institution and country. All educational institutions who were affiliate members at the time of the study were invited to participate (n = 46). Descriptive and thematic analyses are reported. Results: A response rate of 82.6% (n = 38) was achieved from educational institutions representing 21 countries. Over half of responding institutions (n = 21) allocated in excess of 60 European Credit Transfer and Accumulation System (ECTS) credits to practical training. In nearly three-quarters of clinical placements there was a dedicated clinical practice supervisor in place; two-thirds of these were employed directly by the hospital. Clinical practice supervisors were typically state registered radiographers, who had a number of years of clinical experience and had received specific training for the role. Typical responsibilities included monitoring student progress, providing feedback and completing paperwork, this did however vary between respondents. In almost all institutions there were support systems in place for clinical placement supervisors within their roles. Conclusions: Similarities exist in the provision of clinical radiography education across Europe. Clinical placements are a core component of radiography education and are supported by experienced clinical practice supervisors. Mechanisms are in place for the selection, training and support of clinical practice supervisors. Professional societies should work collaboratively to establish guidelines for effective clinical placements. Highlights: First European survey of clinical radiography education. Practical component of radiography programmes deeply embedded. Clinical practice supervision fundamental. Variations between institutions exist.